1941
DOI: 10.3181/00379727-47-13142
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Pure Cultivation of the Smaller Mouth Spirochetes by an Improved Method

Abstract: and probably other factors of the vitamin B complex for norma: growth under the conditions of these studies. Possible factors altering the requirement of choline for dogs on synthetic rations are discussed.The characteristics and properties of the so-called commensal spirochetes of mucous menibraiies, and their individual or contrihuting rbles in fuso-spirochetal infections, remain inadequately understood largely because of a lack of effective nieans for their isolation and maintenance in pure culture. Trepone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

1942
1942
2006
2006

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…Robinson (20) has reported isolation of mouth spirochetes by growing them through filter paper, and Kolmer and Kast (19), using Robinson's method for purification of their strains have isolated mouth spirochetes in liquid media by using high dilutions and selective media. Recently Rosebury and Foley (14) have obtained spirochete growth in small Petri plates, containing a very thick layer of a solid medium.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Robinson (20) has reported isolation of mouth spirochetes by growing them through filter paper, and Kolmer and Kast (19), using Robinson's method for purification of their strains have isolated mouth spirochetes in liquid media by using high dilutions and selective media. Recently Rosebury and Foley (14) have obtained spirochete growth in small Petri plates, containing a very thick layer of a solid medium.…”
Section: Introductionmentioning
confidence: 99%
“…All authors agree that growth of the mouth spirochetes can be obtained only under anaerobic conditions in media containing some enriching substance such as ascitic fluid, serum or blood, whereas the addition of fresh tissue does not seem to be an absolute requirement for all strains. The isolation of the spirochetes has been attempted by many different methods such as centrifugation (21), prolonged incubation (10), selective media (10,18), and most frequently by growth in solid media (10,11,12,13,14,15,16,17). Miihlens (11,12) and Shmamine (15) preferred to cultivate the spirochetes in deep agar shake tubes.…”
Section: Introductionmentioning
confidence: 99%
“…A host-associated treponeme, strain G7201, was isolated from the subgingival plaque of a 52-year-old man with adult periodontitis by a well-plate method (16,24,25). It has been shown that the organism was moiphologically and serologically different from any of the previously established oral Treponema species by the studies using scanning electron microscopy (24,25).…”
mentioning
confidence: 99%
“…Much work has also been done on oral and other non-pathogenic treponemes, e.g. by Rosebury and Foley (1941).…”
Section: Serology Of Syphilismentioning
confidence: 99%